Biomedical waste management practices in a tertiary-care hospital in Punjab - Meenu Kalia, Amrit Virk; BP Gupta; Jasdeep Singh; Meenu Kalia (Universiti Kebangsaan Malaysia, 2015)
Background: Biomedical waste (BMW) has recently emerged as an issue of major concern not only to hospitals and nursing homes, but also to the environmental and law enforcing agencies, media, and the general public. BMW forms approximately 1%–2% of the total municipal solid waste stream. Objectives: The aims of the study were the following: to get background information about the disposal of hospital waste; to determine the awareness regarding waste management practices; to document the waste management practices; and to suggest the possible remedial measures, if required. Subjects and Methods: A cross-sectional study was conducted in a medical college hospital in Patiala district. A survey of the personnel handling and monitoring the BMW was carried out using a scientifically prescribed questionnaire. Results: More than 90% of the nurses and laboratory technicians were well aware of the proper disposal of the sharps and infected waste, but only 50% of the sweepers could satisfactorily answer about the same. Among nurses, approximately 90% were aware that improper management of BMW causes environmental pollution and injuries, whereas 60% of nurses and laboratory technicians could enlist the diseases transmitted by improper handling of BMW. Approximately 40–60% of ward boys and sweepers were aware of the effects of poor handling of BMW on environment and the injuries caused by it, but none of them could tell the diseases transmitted by the improper recycling of hospital waste or by improper handling of BMW. Conclusion: The human element is found to be far more important than the technology. Almost any system of treatment and disposal of BMW that is operated by well-trained and well-motivated staff can provide greater protection to staff, patients, and the community than an expensive and sophisticated system that is managed by staff who do not understand the risk and the importance of their contribution.